1999
DOI: 10.1002/etc.5620181038
|View full text |Cite
|
Sign up to set email alerts
|

Lead effects on the predictability of reproductive behavior in fathead minnows (Pimephales promelas): A mathematical model

Abstract: Lead (Pb) has been shown to affect the behavior of a wide variety of vertebrates, including fish, amphibians, and mammals. This article re-examines previous data on the effect of short-term, sublethal levels of waterborne Pb on the reproductive behavior of fathead minnows (Pimephales promelas). Previous research has found that Pb decreased the time spent in displaying specific reproductive behaviors in male minnows. Because each activity performed within a sequence depends upon previous parts of the sequence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…The autocorrelation properties of animal activity patterns are interesting to study because they may reflect differences in physiological states of animals and their responses to environmental factors in new ways (MacIntosh, Alados, & Huffman, ; MacIntosh, Pelletier, Chiaradia, Kato, & Ropert‐Coudert, ). For example, some studies have shown that physiological stressors (e.g., clinically impaired health, reproductive activities) or other challenges (e.g., low dominance status) are associated with less stochasticity, that is, increasing periodicity or stereotypy (Alados & Weber, ; Alados et al., ; Motohashi, Miyazaki, & Takano, ; Rutherford, Haskell, Glasbey, & Lawrence, ; Seuront & Cribb, ). In contrast, individuals show increased complexity of behavioral patterns when they explore resources in novel environments, which in turn may increase foraging success rates (Alados et al., ; Escos et al., ; Kembro et al., ; MacIntosh et al., ; Shimada, Minesaki, & Hara, ).…”
Section: Discussionmentioning
confidence: 99%
“…The autocorrelation properties of animal activity patterns are interesting to study because they may reflect differences in physiological states of animals and their responses to environmental factors in new ways (MacIntosh, Alados, & Huffman, ; MacIntosh, Pelletier, Chiaradia, Kato, & Ropert‐Coudert, ). For example, some studies have shown that physiological stressors (e.g., clinically impaired health, reproductive activities) or other challenges (e.g., low dominance status) are associated with less stochasticity, that is, increasing periodicity or stereotypy (Alados & Weber, ; Alados et al., ; Motohashi, Miyazaki, & Takano, ; Rutherford, Haskell, Glasbey, & Lawrence, ; Seuront & Cribb, ). In contrast, individuals show increased complexity of behavioral patterns when they explore resources in novel environments, which in turn may increase foraging success rates (Alados et al., ; Escos et al., ; Kembro et al., ; MacIntosh et al., ; Shimada, Minesaki, & Hara, ).…”
Section: Discussionmentioning
confidence: 99%
“…We repeated this procedure for all time scales (box sizes), which were the nearest integers to 2 Previous studies show that a-exponents (described in §1) of observed behavioural sequences differ significantly from randomized surrogate sequences, which result in a % 0.5 [17,19]. We randomized 78 foraging and 85 locomotion sequences collected during October and November 2007, and compared the mean a-exponents of 10 simulated sequences with observed sequences using paired t-tests.…”
Section: Discussionmentioning
confidence: 99%
“…The long‐range spatial autocorrelation of each species determined the degree of spatial clustering of each species' cover, independent of the scale of measurement. Detrended fluctuation analysis (DFA), which describes spatial autocorrelation and patchiness, as opposed to random distribution, was used to detect long‐range spatial autocorrelations (Peng et al ., 1992; Alados & Weber, 1999; Hu et al ., 2001). A large DFA value indicates that what happens in one step depends on what appears in previous consecutive steps across a long sequence.…”
Section: Methodsmentioning
confidence: 99%